A Comprehensive Analysis of the Glutathione Peroxidase 8 (GPX8) in Human Cancer - Ren, Zhijing; He, Yu; Yang, Qinqin; Guo, Jiajia; Huang, Haifeng; Li, Bo; Wang, Dong; Yang, Zhen; Tian, Xiaobin (Frontiers in Oncology, 2022)
Objective: Nowadays, cancer is still a leading public health problem all over the world. However, the prognostic potential of GPX8 in pan-cancer remains unclear. In this work, we aimed to explore the prognostic and immunological role of GPX8 in human cancer and confirm the oncogenic value in GBM cells. Methods: The data of TCGA, CPTAC and GEO databases were adopted for the survival analysis. Based on the RNAseq and Methylation450 data of TCGA, the R language and package “ggplot2” were used to analyze the DNA methylation at the region of the promoter of GPX8 in tumors. The genetic alteration of GPX8 from TCGA cancers was investigated in cBioPortal. The R package “GSVA” and “ssGSEA” were employed to evaluate the correlation of GPX8 expression with the immune infiltration. The KEGG website was used for pathway analysis. The STRING website and GEPIA were performed to predict GPX8-binding proteins. The R package “ggplot2” and “clusterprofile” were used to analyze and visualize the GO and KEGG analysis. A normal human astrocyte cell line and three GBM cell lines were cultured under suitable conditions. The shRNA was transferred to cells by Lipofectamine 3000. The qRT-PCR was adopted to detect the expression of GPX8. The wound-healing assay and transwell assay were taken to analyze the invasive and metastatic abilities. Results: GPX8 was a valuable diagnostic biomarker in multiple cancers, including GBM/LGG, KIRC, KIRP and STAD. Moreover, we observed a correlation between the expression of GPX8 and the reduced DNA methylation at the promoter region in several tumors, such as GBM/LGG. Our results indicated a positive correlation between the GPX8 expression and immune infiltration. In addition, the enrichment analysis demonstrated that glutathione metabolism was mainly involved in the functional mechanism of GPX8. In particular, we first confirmed the up-regulated of GPX8 in GBM cells and observed the suppression of migrative and invasive phenotypes by knockdown of GPX8. Conclusion: Our study showed a correlation of GPX8 expression with clinical prognosis, DNA methylation and immune infiltrates. Furthermore, we first confirmed GPX8 was highly expressed in GBM cells and contributed to migration and invasion.